2017
DOI: 10.1016/j.aott.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the open reduction-internal fixation and resection arthroplasty techniques in treatment of Mason Type 3 radial head fractures

Abstract: ObjectiveThe aim of this study was to retrospectively compare a series of patients surgically treated with ORIF or early resection arthroplasty due to isolated comminuted radial head fractures.MethodsBetween the years 2009 and 2013, 34 patients with isolated comminuted fractures of the radial head (Mason Type 3) had been operated (ORIF in 19 patients, resection arthroplasty in 15 patients). The mean age of the patients in the ORIF group was 38.5 years and 54 years in the resection group. The carrying angle (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Despite increased carrying angle, satisfactory long-term functional results were previously reported. 30,31 Ulnar impaction syndrome is a possible complication after radial head resection. In our study group, there were no complaints regarding ulnar sided wrist pain or complaints about aggravated wrist pain by forceful grip.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased carrying angle, satisfactory long-term functional results were previously reported. 30,31 Ulnar impaction syndrome is a possible complication after radial head resection. In our study group, there were no complaints regarding ulnar sided wrist pain or complaints about aggravated wrist pain by forceful grip.…”
Section: Discussionmentioning
confidence: 99%
“…Radial head arthroplasty (RHA) becoming a more popular option in recent years for the treatment of radial head fracture Mason type III and IV. Many studies state that RHA showed a superior result compared to radial head resection and open reduction and internal fixation, but some were against it, stating that the latter option is better in term of functional outcomes, number of revision surgery and post-operative early and late complications [ 1 , 3 , 4 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…No substantial differences in patient outcomes at medium and long-term follow-up [ 3 ]. A similar study from Akman et al show that resection arthroplasty is an effective method for the treatment of isolated comminuted radial head fractures because of the less demanding technique [ 8 ]. All of our patient in this case series show fairly good functional outcomes even when some papers is saying that radial head resection is better.…”
Section: Discussionmentioning
confidence: 99%
“…They thought ORIF was applicable to severely comminuted radial head fractures, which otherwise would require excision. Akman et al [8] retrospectively compared the clinical results of 34 patients with Mason type III fractures. Nineteen patients received ORIF, and 15 patients underwent radial head resection.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment options include open reduction and internal fixation (ORIF), radial head arthroplasty, and radial head resection. [1,7,8] A radial-head excision may result in some adverse effects, including proximal migration of the radius, decreased strength, elbow and wrist degenerative arthritis, cubitus valgus, and posterolateral rotatory instability of the elbow. [7,9] Because the radial head plays an important role in maintaining the stability of the elbow, many investigators recommend preservation of the radial head, either by ORIF or radial head arthroplasty.…”
Section: Introductionmentioning
confidence: 99%